PERSEPSI MAHASISWA GENERASI Z TERHADAP VOUCHER DISKON TIKTOK DALAM KEPUTUSAN PEMBELIAN - Shafa Fawwas Firzatullah Rachmady; Jessica Inov Tri Agustina Sujarwo; Gloria Tesalonika; Tan Evan Tandiyono (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Changes in consumption patterns among Generation Z, who heavily use social media, have turned TikTok into a social commerce space where discount vouchers can trigger purchase decisions. This study aims to explore Generation Z university students’ perceptions of TikTok discount vouchers and how those perceptions influence purchase decisions. A qualitative approach was employed with data collected via an initial questionnaire, in-depth structured interviews, documentation, and recorded video responses from three purposively selected student informants. Data were analyzed inductively through transcription, thematic categorization, and literative interpretation to capture participants’ subjective meanings. Findings show that TikTok vouchers are viewed favorably by students because they offer lower prices, help reduce daily expenses (especially for food and beverages), and provide ease of access and convenience aligned with Generation Z’s digital lifestyle. The results indicate that economic value (price), utility (accessibility), and platform context (integration with content and affiliates) contribute to purchase decision-making among students. Implications suggest marketers and platform developers should optimize voucher strategies that emphasize cost savings and user convenience while enhancing the overall user experience to improve promotional effectiveness.